Development of Energy Cooperation between Russia and China - An, Jaehyung; Dorofeev, Mikhail; Zhu, Shouxian (International Journal of Energy Economics and Policy, 2019)
The research analyses the question of to what extent the focus on state projects between Russia and China is based on the Russian desire to switch from an economy that is dependent on natural resources. Through the analysis of existing capabilities of the Russian companies to propose opportunities for innovative and technological projects that can be used in the long run. At the same time, the research will focus on energy trends and their presence in Russian and Chinese energy markets. Keywords: Energy Sources, China Energy Policy, Resource Saving, Economic Development, Energy Cooperation. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8509